THE USE OF STUDENT TEAM ACHIEVEMENT DIVISION TO FACILITATE STUDENTS IN READING COMPREHENSION - Maria Ramasari (JELLT (Journal of English Language and Language Teaching), 2020)
This research scrutinizes how Student Team Achievement Division facilitates and affects students in reading comprehension. A pre-experimental design was applied in this research, and it was conducted in six meetings; by giving pretest, four treatments, and posttest. It involved thirty six of the tenth grade students of secondary school at Lubuklinggau, South Sumatera, in Indonesia who attended reading comprehension class. The data were collected by using reading test that was given twice for students; pre-test and post-test were given before and after treatments. The finding of this research disclosed that the students’ average in pretest was 60.00 and in posttest their average score were increased to be 75.00. Based on the result of the paired t-test calculation, it was found that t-obtained 8.196 was higher than t-table 1.684 as the critical value. It meant that the alternative hypothesis (Ha) was accepted. In other words, the use of Student Team Achievement Division was significantly effective to facilitate and affect the students in reading comprehension.